Address at the Sixth Tokyo International Conference on African Development Opening Session - Kim, Jim Yong (World Bank, Washington, DC, 2018)
Jim Yong Kim, President of the World Bank, noted that African countries face key policy challenges including adjusting to a new era of low commodity prices, increasing economic vulnerabilities and the challenge of finding new sources of growth. He feels better at leveraging funds from development partners, stopping illicit financial flows and helping countries mobilize more money domestically. African countries can dramatically increase the flow of private capital to fund infrastructure projects. The World Bank Group is working with African countries and development partners to implement the African Climate business plan which is a comprehensive program and investments totaling US$19.3 billion between 2016 and 2020. Ending stunting everywhere but especially here in Africa is an urgent mission. Universal health care is a critical element to achieve that. Kim called for massive investment, public and private, in infrastructure and universal health coverage for all of Africa.